H HUBUNGAN KEBERAGAMAAN DAN PERILAKU ALTRUISTIK MAHASISWA - Muhamad Ridwan Effendi; Suci Nurpratiwi (Fakultas Agama Islam Universitas Wiralodra, 2021)
This study aims to describe and how the relationship between religiosity and altrusic behavior of students of the Faculty of Social Sciences, State University of Jakarta. This is important to research considering how far the influence of religious education that has been presented in the Jakarta State University curriculum in the form of intracurricular, co-curricular and / or extracurricular activities. The method used in this research is quantitative correlation and probability sampling technique with purposive random sampling with homogeneous data which is used as a sample of 90 people from a population of 898 students. The theoretical analysis used for the religious variable (x) is the theory of the religious dimension of C.Y. Glock and R.W. Stark, while Cohen's theory is used for the altruistic behavior variable of students (y). Based on the results of data analysis, it is concluded that first, student diversity is considered good with an average value of 71.91%. Second, students' alturistic behavior is considered good with an average score of 68.20%. Third, there is a positive and quite significant relationship between religiosity and student altruistic behavior with a correlation value of 0.276 and a percentage of the relationship of 07.6% and there is a positive and significant influence on diversity (X) with student altruistic behavior (Y) at the Faculty of Social Sciences, University. Negeri Jakarta based on the results of the regression calculation by comparing the F count and F table, with F count greater than F table, namely F count = 4.642 and F table = 4.15. So that the alternative hypothesis which states that there is an influence between religiosity on student altruistic behavior is accepted and the null hypothesis which states that there is no influence is rejected.